IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN KESEHATAN (BK) DALAM UPAYA PELAYANAN KESEHATAN GRATIS DI KABUPATEN GIANYAR (Studi Kasus: Rumah Sakit Umum Daerah (RSUD) Sanjiwani) - Sri Widyadewi, Ni Luh Putu; Supriliyani, Ni Wayan; Winaya, I Ketut (CITIZEN CHARTER, 2021)
The Gianyar Regency Government has a Health Assistance Program (BK) for the people of Gianyar Regency which has not been funded by health insurance. This study aims to determine how the policy implementation of the Health Assistance Program in Free Health Services Efforts in Gianyar Regency (Case Study: Sanjiwani Regional General Hospital). The method used is descriptive research method with a qualitative approach and data collection techniques in the form of interviews, observation, and documentation. Analysis using policy implementation theory according to George C. Edward III consists of indicators of communication, resources, disposition, and bureaucratic structure. The results showed that the implementation of the Health Assistance Program was still not optimal as seen from the lack of socialization, lack of staff procurement, absence of accountability reports to the public and limited budget funds. Keyword: Policy Implementation, Health Assistance Program (BK), Free Health Services.